On evidentialiy, particularly in Turkish - Pavelić, Goran (Prilozi za orijentalnu filologiju, 2019)
This informative survey is about the (sub)category of evidentiality, its essential morpho-syntactic features, its areal distribution and linguistic researches in evidentiality. Examples from 22 languages are provided. Then follows the description of evidentiality in Turkic languages, characterized by semantic-pragmatic domain of indirectivity. There are 8 examples from extinct and contemporary Turkic languages. The survey continues with the basic evidential differences of indirectivity in contemporary Turkish. Pragmatic importance of evidentiality is visible in discourse, in mirative expressions and in various narrative genres. There are 29 examples from Turkish. The survey ends with an offer to reader to make her/his decision whether evidentiality is a category or a sub-category. Three different opinions from recent literature are briefly exposed.